2004
DOI: 10.1002/ajim.20099
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of work schedules to gastrointestinal diagnoses, symptoms, and medication use in auto factory workers

Abstract: Findings suggest that evening shift and widely varying work start and end times may increase risks for GI disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 60 publications
2
45
0
6
Order By: Relevance
“…Costa (1996) spricht bei Nachtschichtarbeit von einem 2 bis 5-mal häufigeren Auftreten von Magenbeschwerden. Zudem werden Zusammenhänge zu Magen-und Zwölffingerdarmgeschwüren berichtet (Caruso et al 2004;Knutsson 2003;Segawa et al 1987). Als Ursache von Magen-Darmerkrankungen werden wiederum Störungen des Schlaf-Wachrhythmus angesehen.…”
Section: Problemstellung Und Forschungsstandunclassified
“…Costa (1996) spricht bei Nachtschichtarbeit von einem 2 bis 5-mal häufigeren Auftreten von Magenbeschwerden. Zudem werden Zusammenhänge zu Magen-und Zwölffingerdarmgeschwüren berichtet (Caruso et al 2004;Knutsson 2003;Segawa et al 1987). Als Ursache von Magen-Darmerkrankungen werden wiederum Störungen des Schlaf-Wachrhythmus angesehen.…”
Section: Problemstellung Und Forschungsstandunclassified
“…Several studies have attributed such effects primarily to disruptions in the body's system for regulating circadian rhythms, the so-called biological clock, which helps to stabilize metabolic, endocrine, sleep, and other physiological functions (9)(10)(11)(12). Nonstandard shifts have been associated with sleep disturbances (13)(14)(15), digestive system and eating problems (7,(16)(17)(18), depression and other psychological or nervous disorders (19)(20), cardiovascular disease (7,(20)(21)(22)(23), certain types of cancer (24)(25)(26), and miscarriage (27)(28)(29). It has been suggested that working nonstandard shifts can exacerbate the effects of various systemic diseases including diabetes mellitus and epilepsy (7,20).…”
mentioning
confidence: 99%
“…The shortage of nurses and other types of healthcare workers push those available to work longer hours to fill the vacancies. Studies of many types of workers report these demanding work schedules are associated with several health and safety risks including psychological, gastrointestinal, and cardiovascular disturbances, injuries and automobile crashes, cancer, and adverse reproductive outcomes [1][2][3][4][5][6][7][8][9][10][11][12] . In addition, workers may be more prone to poor health behaviors such as smoking, drug and alcohol abuse and less physical activity.…”
mentioning
confidence: 99%